Orexins in apoptosis: a dual regulatory role - Cavalu, Simona; Saber, Sameh; Hamad, Rabab S.; Abdel-Reheim, Mustafa Ahmed; Elmorsy, Elsayed A.; Youssef, Mahmoud E. (Frontiers in Cellular Neuroscience, 2024)
The orexins, also referred to as hypocretins, are neuropeptides that originate from the lateral hypothalamus (LH) region of the brain. They are composed of two small peptides, orexin-A, and orexin-B, which are broadly distributed throughout the central and peripheral nervous systems.Orexins are recognized to regulate diverse functions, involving energy homeostasis, the sleepwake cycle, stress responses, and reward-seeking behaviors. Additionally, it is suggested that orexin-A deficiency is linked to sleepiness and narcolepsy. The orexins bind to their respective receptors, the orexin receptor type 1 (OX1R) and type 2 (OX2R), and activate different signaling pathways, which results in the mediation of various physiological functions. Orexin receptors are widely expressed in different parts of the body, including the skin, muscles, lungs, and bone marrow. The expression levels of orexins and their receptors play a crucial role in apoptosis, which makes them a potential target for clinical treatment of various disorders. This article delves into the significance of orexins and orexin receptors in the process of apoptosis, highlighting their expression levels and their potential contributions to different diseases. The article offers an overview of the existing understanding of the orexin/receptor system and how it influences the regulation of apoptosis.